An economic analysis of milk production in Haryana - Mohapatra, Soumya; R, Sendhil; Singh, Ajmer; Dixit, A K; Malhotra, R; Ponnusamy, K (Indian Journal of Dairy Science, 2021)
Dairying is an important supplementary enterprise enhancing the livelihood of farmers and hence analyzing its profitability as well as identification of production constraints paves way for policy implications. An attempt was made to determine the costs, returns and constraints involved in milk production at Karnal and Jind districts of Haryana state in 2019-20. Primary data were collected from 120 milk producing households and subjected to tabular analysis and Garrett’s ranking technique. The overall net maintenance cost per animal per day was highest in the case of crossbred, followed by buffalo and indigenous cow. The overall cost of milk production was highest for buffalo (₹40.35/litre), followed by crossbred (₹32.48/litre) and indigenous cow (₹31.88/litre). A major portion in the total variable cost was contributed by the feed and fodder, followed by labour. Net return obtained per litre of milk was positive across animal categories, but it was highest in the case of crossbred owing to higher productivity as compared to buffalo and indigenous cow. Distant location of artificial insemination centres and high price of concentrates were identified as the major production constraints faced by the farmers. The study advocates for adoption of better scientific breeding and management practices, mobile services for quality semen delivery as well as providing feeds at subsidized price channelizing through Farmer Producer Organizations (FPOs). Key words: Cost and returns, Standard animal units, Capital recovery cost, Garrett ranking